Design of a Compact X-Band Substrate Integrated Waveguide Directional Coupler - Ahmad , B. H.; Sabri , Siti Sabariah; Othman , A. R. (2013)
Abstract— This paper presented the design of four-port network directional coupler at X-band frequency (8.2-12.4 GHz) by using substrate integrated waveguide (SIW) technique. SIW appears few years back which provides an excellent platform in order to design millimeter-wave circuits such as filter, antenna, resonator, coupler and power divider. It offers great compensation for smaller size and can be easily integrated with other planar circuits. The fabrication process can simply be done by using standard Printed Circuit Board (PCB) process where the cost of the manufacturing process will be reduced compared to the conventional waveguide. The directional coupler basically implemented at radar, satellite and point-to-point radio. The simulations for this SIW directional coupler design shows good performances with low insertion loss, low return loss, broad operational bandwidth and have high isolation.